Synergizing Social Contract and Stakeholder Theories: An Analysis of Internal Security Preservation in Namibia's Context - Kennedy K. Mabuku; Adewale A. Olutola (UIN Sunan Gunung Djati, 2023)
This study underscores the profound significance of internal security in shaping human existence and offers a timely examination of its contemporary relevance. Faced with escalating threats to societal well-being, the research focuses on the Namibian context to assess the capability of the Namibian Police Force in safeguarding internal security. Through the lens of Social Contract Theory, exemplified by Thomas Hobbes, the study argues that citizens possess a rightful expectation of effective policing, given the relinquishment of certain individual rights to the government. Simultaneously, the research draws on Stakeholder Theory, influenced by Freeman, to advocate for a collaborative approach to security preservation, asserting that while the police play a central role, responsibility should be shared among various stakeholders. This perspective stems from the acknowledgment that the multifaceted nature of contemporary insecurities necessitates a collective effort beyond the capabilities of the police alone. Consequently, the study proposes a constitutional amendment to integrate diverse stakeholders into the realm of internal security, emphasizing a balanced and inclusive strategy to effectively address the intricate landscape of security challenges.